Microvertebrates preserved in mammal burrows from the Holocene of the Argentine Pampas : a taphonomic and paleoecological approach - Tomassini, Rodrigo Leandro (2017)
Fil: Tomassini, Rodrigo Leandro. INGEOSUR-CONICET. Departamento de Geología. Universidad Nacional del Sur. Bahía Blanca; Argentina